Marathon and half marathon : a training guide - Hilditch, Graeme (The Crowood Press, 2014)
The popularity of the marathon and half marathon continues unabated. Up and down the country people are signing up in their thousands, many to raise money for their favourite charity, others simply as a means of getting fit. This book is suitable for anyone intending to enter a half or full marathon